TCP Versus UDP Performance in Term of Bandwidth Usage - Kaytan, Mostfa M. (2010)
This project is mainly about how to establish User Datagram Protocol (UDP) and Transmission Control Protocol (TCP) connection in the same network simulation. For that, we will be using four types of TCP which are TCP Tahoe, TCP Reno, TCP NewReno and TCP Vegas. From there, we are going to differentiate them in term bandwidth usage and define how it works and describes several effect that occurred when its work together. In order to create the topology and run the protocols, we use Network Simulator 2 (NS2) to create and run the coding. To run the codes, we use command which use a few code in running the coding. Then we will get a topology,which is the flow of the packet within the source and destination, base on the coding. A graph also appears after the command.